The Relationship between Education Level and Community Participation in Health Promotion Activities in Pangkajene and Kepulauan Regency, 2025 - Rahmilah, Mitha (Science Tech Group, 2025)
Health promotion is one of the key efforts to improve the community’s health status by enhancing knowledge, attitudes, and healthy behaviors. The success of health promotion programs is strongly influenced by the level of education within the community. Individuals with higher education levels tend to understand and apply health messages more easily, thereby increasing their participation in health promotion activities. This study aimed to determine the relationship between the level of education and community participation in health promotion activities in Pangkajene and Kepulauan Regency in 2025. This research employed a quantitative method with a cross-sectional design. The sample consisted of 467 respondents selected through total sampling. Data were collected using a questionnaire distributed via the KoboCollect application, covering variables of education level and participation in health promotion activities. Data were analyzed using univariate and bivariate analyses with the Chi-Square test at a significance level of p ≤ 0.05. The results showed a significant relationship between education level and community participation in health promotion activities. People with higher education levels tended to be more active in health promotion programs. It is recommended that health centers (Puskesmas) adjust their health promotion methods according to the community’s educational background to improve the effectiveness of health message delivery.